(untitled) (Nigerian Journal of Technology, 2021)
Fresh-water Clawed Lobsters is seafood consumed in its cooked, dried or semi-dried state. Drying is a veritable technology for its storage beyond immediate consumption. This study thus, investigated the drying behaviour of the lobster on thin-layers. A laboratory convective oven dryer was used as the heating source, on the temperature range of 50 – 100 C applied in a varying manner on multiples of 10 C. The layer thickness was about 20-mm. As with high moisture sea foods, the drying profile showed a typical falling rate period with no distinct constant rate period for all the temperature levels used in this work. Moisture loss (diffusion) data obtained from the experiments were fitted to three popular semi-empirical thin-layer models of Page, Lewis, and Henderson-Pabis, respectively, and their suitability was validated using statistical parameters (of R2, RMSE and chi2). This was done to select thin-layer model that would suitably describe the drying kinetics of the samples over the range of temperature levels chosen in this work. Consequently, the Page model and that of Henderson-Pabis respectively were taken to have reliably predicted the drying behaviour of the samples at the chosen temperature levels. The effective diffusivity and the temperature-related activation energy values ranged from 2.239 x 10-8 m2/min - 4.005 x 102/min and 28.5kJ/mol, respectively. Drying rates along with characterizing drying constants and curves also showed an exponential increase with temperature. http://dx.doi.org/10.4314/njt.v40i2.20